Treatment selection and experience in multiple sclerosis: survey of neurologists - Hanson, Kristin A (Dove Medical Press, 2014)
BACKGROUND: Multiple sclerosis (MS) is a complex disease with many therapeutic options. Little is known about how neurologists select particular disease-modifying therapies (DMTs) for their patients. OBJECTIVE: To understand how neurologists make decisions regarding the prescription of DMTs for patients with MS, and to explore neurologists’ experiences with individual DMTs. METHODS: From December 2012 to January 2013, members of a nationwide physician market research panel were sent an online study invitation with a link to a survey website. Eligible neurologists were included if they currently practice medicine in the United States, and if they treat ≥20 patients with MS. RESULTS: A total of 102 neurologists (n=63 general neurologists; n=39 MS specialists; 81.4% male) completed the survey. The mean (standard deviation) number of years in practice since completing medical training was 16.4 (8.6) years. Overall, the most commonly prescribed DMTs were subcutaneous interferon (IFN) β-1a and glatiramer acetate; approximately 5.5% of patients were untreated. The most important attributes of DMT medication selection were (in order of importance) efficacy, safety, tolerability, patient preference, and convenience. The DMT with the highest neurologist-reported percentage of patients who were “Very/Extremely Satisfied” with their therapy was fingolimod (31.0%), followed by glatiramer acetate (13.9%; P=0.017). Compared with fingolimod (94.0%), significantly fewer (P<0.05) neurologists reported that “All/Most” of their patients were adherent to treatment with glatiramer acetate (78.0%), subcutaneous IFN β-1a (84.0%), and IFN β-1b (75.0%); no significant differences were observed with intramuscular IFN β-1a (92.9%; P=0.75). Patients’ calls to neurologists’ offices were most commonly related to side effects for all self-injectable DMTs, whereas calls about fingolimod primarily involved insurance coverage issues. CONCLUSION: Our survey results showed that very few patients with MS did not received any DMT. Among the DMTs available at the time of the survey, neurologists reported that patients were most satisfied with, and adherent to, fingolimod, but these patients also faced more problems with insurance coverage when compared with those taking self-injectable DMTs.